2017
DOI: 10.1093/gbe/evx055
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Evolution of the Kiwifruit Canker Pandemic

Abstract: Recurring epidemics of kiwifruit (Actinidia spp.) bleeding canker disease are caused by Pseudomonas syringae pv. actinidiae (Psa). In order to strengthen understanding of population structure, phylogeography, and evolutionary dynamics, we isolated Pseudomonas from cultivated and wild kiwifruit across six provinces in China. Based on the analysis of 80 sequenced Psa genomes, we show that China is the origin of the pandemic lineage but that strain diversity in China is confined to just a single clade. In contras… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 75 publications
1
126
0
1
Order By: Relevance
“… It has been clarified that biovar 3 had been diversifying for a long time in China, and besides the pandemic lineage, which had spread worldwide, there exist diverse native strains of biovar 3 in China (McCann et al ., ). The characteristics confirmed in the pandemic lineage are shown in this table. …”
Section: Classification and Diversitymentioning
confidence: 97%
See 4 more Smart Citations
“… It has been clarified that biovar 3 had been diversifying for a long time in China, and besides the pandemic lineage, which had spread worldwide, there exist diverse native strains of biovar 3 in China (McCann et al ., ). The characteristics confirmed in the pandemic lineage are shown in this table. …”
Section: Classification and Diversitymentioning
confidence: 97%
“…Moreover, it is also confirmed that the genetic diversity of these domestic biovar 1 strains is relatively large (Fig. ; Sawada et al ., ; McCann et al ., ). On the other hand, in addition to Japan, a small number of biovar 1 strains have also been detected in kiwifruit in Italy and Korea (a strain derived from Italy is indicated by the stars in Figures and ) (Mazzaglia et al ., ; Scortichini et al ., ; Cameron & Sarojini, ; Ciarroni et al ., ; McCann et al ., ).…”
Section: Psa Biovars Found In Japan and Their Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations